An investigation of the utilization of ERP system: a case study at Transwater Sdn Bhd (TW) / Nurul Ashikin Ibrahim - Ibrahim, Nurul Ashikin (2015)
Organizations expend a great deal of time, effort and money on the, implementation of enterprise resource planning (ERP) systems. They are considered the price of entry for organizations to do business. Yet the success rate of ERP Systems is poor. Information System (IS) literature suggests that one possible reason for this is the underutilization of these systems. Existing ERP literature is replete with research to improve ERP project implementation success; however, notably absent from these streams is the research that identifies how ERP systems are utilized by individuals or organizations. This IT Project empirically examined the utilization of ERP system in an organization, which is Transwater Sdn Bhd. In specific, there were three (3) objectives in this study as the following; to investigate the utilization level of ERP system in Transwater Sdn Bhd, to identify the factors that influence the ERP utilization, and to examine the relationship between the determined factors with the utilization of ERP system. A survey was conducted with 62 respondents within the company. The methods used to analyze data are reliability analysis, frequency distribution, descriptive statistic, bivariate regression and multiple regressions in order to achieve the objectives outlined. The findings showed that searching features were the most utilized features by users. Utilization level of ERP system was found under 'unacceptable' category. Lastly, result also showed that there was no significant relationship between Experiential Interventions (EI) factor with Utilization of ERP System (UOES). The remaining three (3) studied factors had significant relationship with the Utilization of ERP System.